Case Report: Hyperprolinemia type II in a child with autism spectrum disorder and ALDH4A1 gene variant in a consanguineous family - AlQurashi, Faisal O.; Alawam, Bashayer S.; Alhaddad, Bader; Alrebh, Zahra A. (Frontiers in Pediatrics, 2026)
Hyperprolinemia type II (HPII) is a rare inherited metabolic disorder caused by the ALDH4A1 gene variant. Herein, we report a case of a preschool-aged Saudi girl who was born from consanguineous parents and presented with global developmental delay. The patient was clinically diagnosed with autism spectrum disorder with associated disruptive behaviors. Metabolic investigations revealed markedly elevated plasma and urinary proline levels, suggestive of a proline metabolism disorder. Whole-exome sequencing identified a homozygous variant of uncertain significance in the ALDH4A1 gene, which is associated with autosomal recessive HPII. Genetic testing of the patient's family members showed that all individuals had carrier status with varying zygosity. This case underscores the importance of metabolic and genetic evaluation in children with neurodevelopmental disorders and highlights that HPII can present with a clinical phenotype that overlaps substantially with ASD.